Shaping the Royal Navy : technology, authority and naval architecture, c.1830-1906 - Leggett, Don (Manchester University Press, 2015)
The 19th-century Royal Navy was transformed from a fleet of sailing wooden walls into a steam powered machine. Britain's warships were her first line of defence, and their transformation dominated political, engineering and scientific discussions. They were the products of engineering ingenuity, political controversies, naval ideologies and the fight for authority in 19th-century Britain. This book provides a cultural history of technology, authority and the Royal Navy in the years of Pax Britannica.